Brain morphophysiology of Africanized bee Apis mellifera exposed to sublethal doses of imidacloprid - De Almeida Rossi, Caroline [UNESP]; Roat, Thaisa Cristina [UNESP]; Tavares, Daiana Antonia [UNESP]; Cintra-Socolowski, Priscila [UNESP]; Malaspina, Osmar [UNESP] (Springer Nature, 2013)
Several synthetic substances are used in agricultural areas to combat insect pests; however, the indiscriminate use of these products may affect nontarget insects, such as bees. In Brazil, one of the most widely used insecticides is imidacloprid, which targets the nervous system of insects. Therefore, the aim of this study was to evaluate the effects of chronic exposure to sublethal doses of imidacloprid on the brain of the Africanized Apis mellifera. The organs of both control bees and bees exposed to insecticide were subjected to morphological, histochemical and immunocytochemical analysis after exposure to imidacloprid, respectively, for 1, 3, 5, 7, and 10 days. In mushroom bodies of bees exposed to imidacloprid concentrations of LD50/10 and in optic lobes of bees exposed to imidacloprid concentrations of LD 50/10, LD50/100, and LD50/50, we observed the presence of condensed cells. The Feulgen reaction revealed the presence of some cells with pyknotic nuclei, whereas Xylidine Ponceau stain revealed strongly stained cells. These characteristics can indicate the occurrence of cell death. Furthermore, cells in mushroom bodies of bees exposed to imidacloprid concentrations of LD50/10 appeared to be swollen. Cell death was confirmed by immunocytochemical technique. Therefore, it was concluded that sublethal doses of imidacloprid have cytotoxic effects on exposed bee brains and that optic lobes are more sensitive to the insecticide than other regions of the brain. © 2013 Springer Science+Business Media New York.
Keywords: imidacloprid; bee; brain; dose-response relationship; entomology; morphology; nontarget organism; sublethal effect; animal experiment; Apis mellifera; controlled study; drug cytotoxicity; Feulgen staining; histochemistry; immunocytochemistry; LD 50; long term exposure; mushroom body; nonhuman; optic lobe; priority journal; Brazil; Apoidea; Basidiomycota; Hexapoda